Aesthetic rehabilitation with prefabricated composite resin veneers: case report (Research, Society and Development, 2020)
Introduction: Facial harmony depends on the disposition, alignment and position of the teeth, which, when they are in an appropriate geometry, translate the expression of what is beautiful. One of the problems found is the imbalance in the harmony of the smile caused by changes promoted by fractured incisal edges, poor dental positioning, diastemas, among others. In this sense, prefabricated composite resin facets, such as pre-polymerized composite laminates, appeared on the market to simplify the restorative procedure and allow the aesthetics and harmony of the smile. Objective: To describe the use of prefabricated resin veneers in previous aesthetic rehabilitation. Case report: Patient, female, 46 years old, attended the dental clinic 42 years old, female, attended the Integrated Clinic of the Faculty of Dentistry of UFRJ complaining about the aesthetics of her smile. On clinical examination, staining and poor restoration were observed in teeth 11 and 21, in addition to the presence of diastema. The treatment plan consisted of using prefabricated facets of composite resin, acid conditioning and adhesive, according to the manufacturer's recommendations. Conclusion: The use of veneers allows a high aesthetic standard in anterior teeth through a minimally invasive technique. As described in this case report, it has great clinical applicability and ease in performing the restorative technique.